2020
DOI: 10.1097/prs.0000000000007458
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surgical Timing on 30-Day Outcomes in Cleft Palate Repair

Abstract: Background: The optimal age for cleft palate repair continues to be debated, with little discussion of surgical risk related to operative timing. This study of 3088 cleft palate patients analyzed the impact of surgical timing on perioperative and 30-day postoperative outcomes. Methods: Primary cleft palate repairs were identified in the National Surgical Quality Improvement Program database from 2012 to 2015. Data were combed for total postoperative com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…6,7 While recommended timing guidelines for cleft operations exist, there is still considerable debate over the ideal timing for different procedures. 8,[11][12][13][14] Furthermore, national trends in the surgical timing of these orofacial procedures have yet to be described. Using the NSQIP-P database, this study characterizes the national trends in the ages for common orofacial operations with respect to advised timing recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 While recommended timing guidelines for cleft operations exist, there is still considerable debate over the ideal timing for different procedures. 8,[11][12][13][14] Furthermore, national trends in the surgical timing of these orofacial procedures have yet to be described. Using the NSQIP-P database, this study characterizes the national trends in the ages for common orofacial operations with respect to advised timing recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria for patients undergoing primary cleft palate repair included the CPT codes of 42225 (palatoplasty for cleft palate, attachment pharyngeal flap) and 42215 (palatoplasty for cleft palate, major revision). 8 Patients undergoing cleft lip revision or cleft palate revision were identified using the CPT codes of 40720 (secondary repair of a cleft lip and or nasal deformity) or 42215 (palatoplasty for cleft palate, major revision), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent reports from large databases have shed light on the impact of timing on early versus late complications (ie, 30 days 31 versus 2000 days, 32 respectively). Overall, it was found that early repair was associated with worse outcomes at both endpoints.…”
Section: Surgical Optimization and Timingmentioning
confidence: 99%
“…NSQIP patients ( n = 3088) who underwent single-stage repair before 6 months of age experienced a two-fold increase in 30-day complication rates ( P = 0.04) and a four- to five-fold increase in readmissions ( P = 0.02) and reoperations ( P = 0.04) within the same timeframe (level of evidence: III). 31 With respect to 2000-day complication rates, a large database project using the IBM MarketScan Commercial Database ( n = 3046) identified that patients were more likely to require a secondary procedure if primary repair occurred before 10 months of age. However, patients were 60% less likely to require a secondary procedure if initial repair occurred between 10 and 14 months of age ( P < 0.001) and 29% less likely if initial repair occurred at more than 14 months of age ( p = 0.002) (level of evidence: III).…”
Section: Surgical Optimization and Timingmentioning
confidence: 99%